2020
DOI: 10.1016/j.bioelechem.2020.107500
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and limitations of MFC anodic community when exposed to antibacterial agents

Abstract: Highlights MFC cascade can withstand and degrade high concentrations of ampicillin. Chloroxylenol caused loss of power and microbial community within MFC cascade. MFC anodic biofilm responds differentially to different inhibitory chemical agents. MFC cascade has the potential for bioremediation of certain chemical agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated that both Proteobacteria and Firmicutes were defined as the most common EABs in MFC reactors (Logan and Regan 2006;Wang et al, 2019;Tao et al, 2020). The microorganisms of various genera in the Proteobacteria phylum play important roles in degrading substrates and generating electricity (Obata et al, 2020). Cheng et al (Cheng et al, 2021) noted that the high EAB abundances in both devices would have promoted COD removal, and the results confirmed that this did occurred.…”
Section: Analysis Of System Community Compositionmentioning
confidence: 71%
“…Previous studies demonstrated that both Proteobacteria and Firmicutes were defined as the most common EABs in MFC reactors (Logan and Regan 2006;Wang et al, 2019;Tao et al, 2020). The microorganisms of various genera in the Proteobacteria phylum play important roles in degrading substrates and generating electricity (Obata et al, 2020). Cheng et al (Cheng et al, 2021) noted that the high EAB abundances in both devices would have promoted COD removal, and the results confirmed that this did occurred.…”
Section: Analysis Of System Community Compositionmentioning
confidence: 71%